Assessing the Impact of Land Use on Dew Yield Using Remote Sensing Data in Taiwan - J. J. Lin; A. N. Arslan; A. N. Arslan (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Dew condensation plays a significant role in hydrological cycles and resource management, particularly in regions with diverse climatic and land use conditions. This study integrates the Nocturnal Condensation Potential Index (NCPI) with satellite-derived Leaf Area Index (LAI) and Land Use/Land Cover (LULC) data to evaluate dew condensation potential across Taiwan from May 2016 to April 2017. NCPI, based on air temperature, dew-point differences, and relative humidity. The integration of NCPI with LAI resulted in the LAI-derived Condensation Potential (LCP), capturing spatial and temporal variations in condensation potential. Key findings include higher NCPI values during the cold season, higher LCP values in dense forested areas, and greater variability in urban and riverine environments. Trees consistently exhibited the highest LAI and the lowest variability, while urban and riverine areas showed significant heterogeneity in condensation potential. Seasonal differences revealed higher dew condensation potential during the cold season, with implications for hydrology and resource management. This research enhances understanding of dew condensation dynamics and highlights its potential applications in agriculture, urban planning, and sustainable water resource management. The findings underscore the importance of integrating meteorological and satellite-derived indices to evaluate dew formation patterns in diverse landscapes. Future work should explore finer-scale microclimatic interactions and the viability of dew harvesting in water-scarce regions.